What About the Child? Toward a Catholic Soteriology of Aborted Fetuses - Olen-Thomas, Collin (Journal of religion and health, 2025)
In this essay, I utilize a historical methodology into Catholic thought on abortion, looking toward the foundational viewpoint of original sin as justification for the need to baptize infants for the sake of their salvation. Then, I highlight how abortion has developed and shifted throughout the twentieth century vis-à-vis Papal Encyclicals and Vatican II. Strikingly, there is a resounding silence on the soteriology of aborted fetuses in Canon Law. Finally, I return to the clinical context to indicate the theological tension between the Catholic Church’s foundational belief on the need to baptize and their procedural ethic on the soteriology of aborted fetuses, resulting in the uncertainty of the salvation for unbaptized aborted fetuses.